Collaboration between tuberculosis control programs and the action plan for tackling antimicrobial resistance: An opportunity in the Eastern Mediterranean Region. (December 2016) - Hasan, Rumina; Shakoor, Sadia; Baghdadi, Samiha; Mafi, Alireza; Aziz, Mohammad
Abstract: Objective/background: Over-the-counter availability of antibiotics together with poor access to diagnostics is recognised to promote antimicrobial resistance (AMR) including generation of drug-resistant tuberculosis (DR-TB). In accordance with the End TB Strategy target of ending TB epidemic by 2030, efforts to control DR-TB are ongoing in Eastern Mediterranean Region (EMR) countries, a number of which have well-established facilities for diagnostics, disease care and prevention as well as surveillance. These could serve as models for AMR control. The United Nation's historic 2016 declaration recognises AMR as a threat to health, food production and development, and emphasises the need for global action. In view of this declaration, establishment of collaboration between the DR-TB and AMR activities would be mutually beneficial and lead to strengthening of both programs. Methods: Available information on TB control and AMR programs in EMR was reviewed. To assist with policy and planning strategies for promoting collaboration between AMR and TB, control activities were explored. Results: Review of available information suggests gaps in TB care in many countries in EMR, most of which are linked to limited access to resources. At the same time, the fledgling AMR programs have a lot to learn from the experiences, successes and challenges faced by TB control efforts. A logic model is presented to enhance interprogram collaboration. Conclusions: Given the global commitment and potential availability of resources towards controlling AMR, collaboration between the two programs is discussed towards a more efficient use of resources in the region.